2023
DOI: 10.3390/molecules28227459
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds in Fractionated Blackcurrant Leaf Extracts in Relation to the Biological Activity of the Extracts

Monika Staszowska-Karkut,
Barbara Chilczuk,
Małgorzata Materska
et al.

Abstract: The aim of this study was to determine the relationship between antioxidant and anticancer properties of extracts from blackcurrant (Ribes nigrum L.) leaves and their fractions and chemical contents. Dried ethanolic extract was divided into three fractions using solid phase extraction: aqueous (F1), 40% MeOH (F2), and 70% MeOH (F3). Both the extract and the fractions were analyzed in terms of antiradical activity (DPPH• and ABTS+•), total phenolic compounds, and total flavonoids. The antitumor potential of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…This aligns with the core tenets of the circular economy, advocating for the efficient utilisation of resources and the adoption of contemporary processing methodologies. Byproducts encompass not only pomace resulting from juice or oil extraction but also various other plant morphological components, such as leaves (e.g., black currant), husks, stems, peels, and seeds, as specified by Staszowska-Karkut et al [ 44 ], Blejan et al [ 39 ], and Wójciak et al [ 45 ], which exhibit substantial polyphenol and fibre content. Leveraging such byproducts represents a reservoir of valuable nutrients, recognised as a cost-effective resource offering manifold health benefits for both consumers and producers, fostering an environmentally sustainable and economically viable food chain [ 46 ].…”
Section: Further Perspective Of Developmentmentioning
confidence: 99%
“…This aligns with the core tenets of the circular economy, advocating for the efficient utilisation of resources and the adoption of contemporary processing methodologies. Byproducts encompass not only pomace resulting from juice or oil extraction but also various other plant morphological components, such as leaves (e.g., black currant), husks, stems, peels, and seeds, as specified by Staszowska-Karkut et al [ 44 ], Blejan et al [ 39 ], and Wójciak et al [ 45 ], which exhibit substantial polyphenol and fibre content. Leveraging such byproducts represents a reservoir of valuable nutrients, recognised as a cost-effective resource offering manifold health benefits for both consumers and producers, fostering an environmentally sustainable and economically viable food chain [ 46 ].…”
Section: Further Perspective Of Developmentmentioning
confidence: 99%
“…The fruits are consumed in fresh form or as juices, jams, jellies, and syrups. The leaves and pomace are valuable raw materials with phenolic concentrations and profiles different from the fruit's [4]. Some studies found no correlation between polyphenol profiles in different morphological plant parts.…”
Section: Introductionmentioning
confidence: 99%